2018
DOI: 10.14233/ajchem.2019.21667
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Process of Essential Oil from Plectranthus amboinicus Using Microwave-Assisted Hydrodistillation and Evaluation of It’s Antibacterial Activity

Abstract: Plectranthus amboinicus oil has many applications in pharmaceutical, medicine and cosmetic industries. Recently, new methods of extracting essential oil used have been increasingly developed to replace traditional methods. In this study, maximization of essential oils yield from P. amboinicus was studied by the combination of microwave assisted hydro-distillation (MAHD) and response surface methodology (RSM). We found that that the maximum essential oil yield was 0.1374 % with 94.38 % reliability and influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 13 publications
(12 reference statements)
0
13
0
Order By: Relevance
“…In Agar diffusion assays, drugs with antimicrobial potential show a growth inhibition halo with diameter proportional at its antimicrobial potential and, strong antimicrobial potentials are considered when halos with at least 15 mm of diameter are achieved [20]. According to with this parameter, P. amboinicus essential oils have strong antimicrobial activity against several strains as Staphylococcus aureus [21][22][23][24][25][26], MRSA, S. epidermidis, Enterococcus faecalis [25], Aeromonas caviae [21], Proteus vulgaris [21],…”
Section: Agar Diffusion Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Agar diffusion assays, drugs with antimicrobial potential show a growth inhibition halo with diameter proportional at its antimicrobial potential and, strong antimicrobial potentials are considered when halos with at least 15 mm of diameter are achieved [20]. According to with this parameter, P. amboinicus essential oils have strong antimicrobial activity against several strains as Staphylococcus aureus [21][22][23][24][25][26], MRSA, S. epidermidis, Enterococcus faecalis [25], Aeromonas caviae [21], Proteus vulgaris [21],…”
Section: Agar Diffusion Methodsmentioning
confidence: 99%
“…For studies raise and in many cases, the growth inhibition potential of P. amboinicus essential oil was higher than standard drugs as [22,26], where P. amboinicus essential oil showed most efficiency that than the drugs Cefepime and Gatifloxacin [22]. Another study showed higher inhibition zones for the essential oil in relation to vancomycin against gram-positive bacteria and cefotaxime against E. coli [25].…”
Section: Agar Diffusion Methodsmentioning
confidence: 99%
“…The selected experiment design was Central Composite Design, and the experimental matrix was built using Design-Expert 11.0 software. [28][29][30][31] Antioxidant Activity of CJR Extract Test for radical scavenging activity using the DPPH method. The extract was first diluted to a reasonable concentration.…”
Section: Optimization Using Rsmmentioning
confidence: 99%
“…On the contrary, the large peel sizes will yield lesser oil due to small surface area in contact with the solvent. Therefore, grind peels have been chosen in subsequent investigations (Dao et al, 2019b;.…”
Section: Single Factor Investigationmentioning
confidence: 99%